Why Britain Can't Afford Informed Consent - Schwartz, Robert (The Hastings Center report, 1985)
In the case of Mrs. Amy Sidaway, the House of Lords has rejected the “American” legal doctrine of informed consent, which is based on patients' rights, in favor of a standard based on the obligations of the reasonable physician. The British National Health Service, with centralized planning, prospective funding, and limited resources, is unlikely to provide a safe harbor for a doctrine based on individual choice in health care.